Dielectric-core conical-horn antennas with rectangular-waveguide feed for point-to-point millimeter-wave communication. - Boryssenko, Anatoliy O.
High-efficiency antennas are required for millimeter-wave communications with low-power solid portable components. In this work, a family of optimized antennas, based on a conical-horn antennas with a combined dielectric element for matched feed and pattern correction, is presented. Thanks to the optimization of the geometry of this element, the proposed antennas show low return losses and good patterns within a 32-36 GHz frequency band. The approach that is employed in this work makes it possible to develop optimized antenna candidates for millimeter-wave portable communication systems. Experimental samples of antennas with "wide" and "narrow" beams are presented and discussed.
Keywords: Millimeter-wave antenna; Conical horn antenna; Dielectric tapered rod antenna; Dielectric lens antenna; Rectangular waveguide; Circular waveguide; Dielectric waveguide